The effectiveness of lecture and discussion methods on adolescent behavior in the treatment of the external genetalia at Yayasan Pendidikan Keluarga high school, Medan - Harahap, Rizki Noviyanti; Bima Suryantara; Siti Saidah Nasution (Jurnal EduHealth, 2024)
Background: One factor that causes cervical cancer is the lack of personal hygiene in the genital organs. However, there are still young women who do not maintain the cleanliness of their genital organs, in fact, it is better to be aware of the importance of maintaining the cleanliness of the external genital organs from an early age. Problems that arise due to poor hygiene of the genital organs, namely the emergence of several venereal diseases such as vaginal discharge, genital skin irritation, allergies, cervical cancer, urinary tract infections, one of the efforts to increase knowledge of young women, provides information on external genital care. The aim of the research is to find out the effectiveness of the lecture and discussion method on the behavior of young women in the care of external genitalia.Research Methods: The research design uses a quasi-experimental approach with the Two Group Pretest Posttest approach, namely by using a comparison group but at least observations have been made. The population of this study was all young women at the Medan Family Education Foundation High School totaling 242 people. The sampling technique is simple random sampling. The total sample is 70 people consisting of 35 lecture groups and 35 discussion groups. bivariate analysis with T-test. Results: The results showed that the discussion method was more effective than lectures on the behavior of young women in treating external genitalia. There was a difference in the average score of knowledge of young women in treating external genitalia. Changes in knowledge are greater using the discussion method with an average value of 2.97 compared to lectures with an average value of 0.52. Changes in attitude were greater using the discussion method with an average value of 14.13 compared to lectures with an average value of 0.72. Changes in action were greater using the discussion method with an average value of 6.12 compared to lectures with an average value of 0.76. Conclusion: The discussion method is more effective for improving the behavior of young women in caring for external genitalia at the Medan Family Education Foundation High School.